Mapping Accounting Literacy And Financial Literacy In Business Education: A Bibliometric Analysis - Yusuf, Yusuf; Andrianto, Ahmad; Handayati, Puji; Restuningdiah, Nurika (PT. EQUATOR SINAR AKADEMIA, 2025)
The research discusses the mapping of accounting literacy and financial literacy in business education which is increasingly important for students now. The purpose of this study is to determine the most popular research topics to be researched over the past ten years with bibliometric analysis. This research filters articles from the Scopus database from 2015 to 2025 using VOSviewer analysis software. A total of 1654 articles were accessed through various filtering processes. This study distributes the results based on the year of publication and the most researched articles. The findings explain that financial literacy is a topic of discussion that is often used by researchers. While the integration of accounting literacy and digital literacy in business education is still a little research. The implications of this research encourage the education curriculum to improve accounting literacy and digital literacy skills in order to adapt to technological developments.